(untitled) (Journal of Fiber Bioengineering and Informatics, 2019)
With the rapid development of photonic crystals (PCs), PC structural colouration has gained great attention from many more researchers. Dyeing methods can benefit a lot from PC structural colours and become more environmentally friendly. This modified colouration is superior to the traditional ordinary and chemical dyes and pigments, because of the special characteristics of PC structural colours, such as high brightness, high saturation, never fading, iridescent effect, polarization phenomenon, and so on. In this work, the concept and clarification of PCs, the PC structural colour, the mechanism of structural colouration and various methods of preparing artificial PC are reviewed. Generally, PC can be divided into different types because of diverse spatial distribution characteristics of the photonic band gap. The basic principle of the structural colouration is explained in detail. In the process of producing structural colour, it is of great importance to synthesize silica nanoparticles by solvent change technique (SVT) and self-assembly gravity sedimentation method is described minutely in this paper. Meanwhile, the strengths and weakness of these methods are compared to select the best method for manufacturing structural colours. The applications of PC structural colour are summarized, and some problems are proposed which need to be solved in PC development in the future.